Further study of the genus Mycterothrips Trybom (Thysanoptera: Thripidae) in Japan, with description of a new species and a new record - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2024)
Mycterothrips albiziae sp. n. is described from Albizia julibrissin in Japan. Mycterothrips auratus is newly recorded from Japan and redescribed, second instar larvae of M. fasciatus and M. japonicus are described for the first time. Host plants and character states variation of some Japanese species of Mycterothrips, an identification key to the Japanese species, and a list of world Mycterothrips species is also provided.